PERLINDUNGAN HUKUM MEREK TERKENAL TERHADAP PELAKU BAD APPLICANT DALAM PENDAFTARAN MEREK DI INDONESIA - Danio Stevanno Hallatu, - (2019)
In this global era, international trade can no longer be avoided by countries in the world. This international trade is important for the countries of the world, because in reality the international trade has become the backbone of the country to be prosperous, prosperous, and strong. In the world of trade, the brand as a form of Intellectual Property Rights (IPR) has been used hundreds of years ago and has an important role because the brand is used to distinguish the origin of goods and services. Judging from the infringement or falsification of well-known brands in general is against well-known trademarks or services from abroad. In addition, many well-known brands registered by bad applicants (applicants with bad intentions) still qualify to be registered with the Directorate General of Intellectual Property Rights. In this study, the method used is a type of normative juridical research, with the nature of descriptive research, and analyzed using qualitative methods. Legal protection for well-known brands in Indonesia is growing rapidly after many parties commit fraud, especially after the world of commerce is progressing and developing rapidly. Brand legal protection given to foreign or local, famous or not well-known brands is only given to registered brands. A mark can only be registered on the basis of an application submitted by the owner or his proxy. Application for trademark registration is submitted in writing to the Directorate General of Intellectual Property (DJKI) based on Government Regulation Number 23 of 1993 concerning Procedures for Application of Trademark Registration. The legal consequences that can be caused by parties who violate brand registration are regulated in Law Number 20 of 2016 concerning Trademarks. In this case, the Directorate General of Intellectual Property Rights has a very strategic role in providing legal protection against trademark registration in Indonesia.